Molecular Docking, Molecular Dynamic Simulation, ADMET, Synthesis, and Preliminary Cytotoxic Activity of New Triazole-Based Derivatives with Expected Histone Deacetylase Inhibition Activity - Zaid Mahmood Mohammed; Ayad Abed Ali Al-Hamashi (Iraqi Journal of Pharmaceutical Sciences, 2025)
Targeting histone deacetylase enzymes (HDACs) is an effective way to treat a variety of diseases, including cancer. A number of HDAC inhibitors (HDACi) have been clinically used. Most of the clinically used HDACi are pan-inhibitors and have poor pharmacokinetic properties. Therefore, several attempts are ongoing to develop new HDACis with optimum structural features to overcome the structural limitations. In this work, six new triazole-based compounds (k1-k6) were proposed via special modification of common pharmacophores of HDACi using 1,2,4-triazole as a zinc-binding group (ZBG), diverse group in CAP group, and hydrophobic linker. These compounds were analyzed by docking study against HDAC6, HDAC2, and HDAC8. The docking study revealed that the proposed compounds has docking score of k1 [(E)-4-((thiazol-2-ylimino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-8.54 Kcal/mol)], k2 [(E)-4-((phenylimino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-8.47 Kcal/mol)], k3 [(E)-4-((p-tolylimino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-8.46 Kcal/mol)], k4 [(E)-4-((naphthalen-2-ylimino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-8.32 Kcal/mol)], k5 [(E)-4-(((4-bromophenyl)imino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-7.62 Kcal/mol)], k6 [(E)-4-(((4-methoxyphenyl)imino)methyl)-N-(1H-1,2,4- triazol-3-yl)benzamide (-6.77 Kcal/mol)], and vorinostat (-9.1 Kcal/mol) against HDAC8. The final compounds were synthesized using conventional organic synthesis methods starting from amide bond formation using the coupling reagents EDCi, DMAP, HOBt, and DIPEA, followed by a Schiff base reaction between the produced aldehyde and various amines to afford the final compounds. All reactions were monitored via TLC plates, and purified using recrystallization and/or column chromatography. The chemical structure for the intermediate and final compounds was characterized using IR and NMR spectroscopy. The preliminary MTT assay of compounds k1, k2, and k5showed a comparable antiproliferative activity with vorinostat against HeLa cells with IC50 values for compound k1 (4.9 µM), k2 (5.3 µM) and k5(5.3 µM) while IC50 for vorinostat was (8.4 µM). Most interestingly, compound k5 showed higher antiproliferative activity against A549 lung cancer cells with an IC50 value (4.4 µM) in comparison to vorinostat (9.5 µM), while compounds k1, k2, and k6 have lower cytotoxic effects with IC50 of (19.2, 17.6, and 10.6 µM) respectively.